General Anesthetic Management of a Child With Horseshoe Lung and Left Lung Hypoplasia for Cheiloplasty: A Case Report. Issue 8 (15th October 2018) - Sato(Boku), Aiji; Morita, Maki; Ota, Haruko; Kamimura, Yuji; Ito, Hidekazu; So, MinHye; Tamura, Tetsuya; Kako, Eisuke; Harada, Jun; Sobue, Kazuya
Abstract : Horseshoe lung is an extremely rare congenital malformation in which the right and left lungs are fused due to stenosis of the lung parenchyma. In anesthetic management, it is important to avoid hypoxemia and hypercapnia caused by a decline in lung capacity and functional residual capacity. A 3-year-old boy with horseshoe lung and left lung hypoplasia was scheduled to undergo cheiloplasty. Regarding respiratory management, to prevent hypoxemia and hypercapnia, we avoided intraoperative peripheral airway obstruction with positive end-expiratory pressure, set a long inspiratory phase time for sufficient alveolar expansion, and maintained sufficient gas exchange in lungs with low reserve capacity.